(3eNJda GdTjYI aj CMcGe GdTQjYIs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3eMeO Hf CMeO GdehShjs)
(3ChdgG (B:s
(3cJGH GdhOjYI hCfhGYgG hajg aUhd(B...s
(3BNQgG (B:s
...(3hbO Qhi CUMGHfG Cf GdSGMQ jbJd hGdhLg aj gPg GdQhGjI Cf gPG ef GdSGMQ EaSGO aj GdCQV(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B227s
(3EjVGM Gdecfhf(B:(3L(B2(3,U(B451s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis